PENGARUH PARTISIPASI ANGGARAN DAN KEJELASAN SASARAN ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN KOMITMEN ORGANISASI DAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERATING (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Bengkalis) - Algenti Zurlaili Sofia; Raja Adri Satriawan Surya; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Budgetary slack is a dysfunctional condition which can be done by managers at middle and lower levels if these organizations implement participatory budgeting. This study aims to examine the effect of participatory budgeting and budget goal clarity on budgetary slack and examine the influence of organizational commitment and leadership style as moderating .The results shows that: 1) participatory budgeting influence to budgetary slack with significance value 0,000 < 0,05. 2) budget goal clarity influence to budgetary slack with significance value 0,000 < 0,05. 3) organizational commitment as to moderate the effect of participatory budgeting on budgetary slack with significance value 0,042 <0,05. 4) organizational commitment as to moderate the effect of budget goal clarity on budgetary slack with significance value 0,002 < 0,05. 5) leadership style as to moderate the effect of participatory budgeting on budgetary slack with significance value 0,047 < 0,05. 6) leadership style as to moderate the effect of budget goal clarity on budgetary slack with significance value 0,000 < 0,05. The result of this study prove participatory budgeting and budget goal clarity influence to budgetary slack and organizational commitment and leadership style able to moderate the effect of participatory budgeting and budget goal clarity on budgetary slack.Keyword : budgetary slack, participatory budgeting, budget goal clarity, organizational commitment , and leadership style.